Interaction between Fusarium udum and wilt susceptible and resistant pigeonpea genotypes: Fungal growth and histopathology - and C.R. BHATIA*, R.N. PANDEY, S.E. PAWAR (Indian Phytopathology, 2002)
Seedlings (15-day-old) of wilt susceptible and resistant Cajanus cajan genotypes TT6 and ICP8863, respectively, were grown in test tubes containing a spore suspension (107 spores/ml) of F. udum. Fungal spread inside the host, and changes in tissues, were investigated at 4, 8 and 12 days after inoculation (DAI). Stem segments from the base, middle and top of the seedlings were plated on PDA for fungal growth. Rapid spread of fungus in TT6 compared with ICP8863 was observed. In 2 independent experiments, 77-80% top segments from TT6 showed fungal growth 12 DAI, compared with 20-33% in the resistant ICP8863. Transverse sections from the root and stem segments were examined for changes in tissues. A number of xylem vessels in root and stem were clogged and brown in colour in TT6 seedlings, while in ICP8863, they were either free from any deposit or partially occluded. The wilt resistance in ICP8863 was due to slow growth and localization of the pathogen.